Detection of Cryptic taxa in the genus Leptophryne (Fitzinger, 1843) (Amphibia; Bufonidae) and the description of a new species from Java, Indonesia - Hamidy, Amir; Munir, Misbahul; Mumpuni, Mumpuni; Rahmania, Mila; Kholik, Azis Abdul (Zootaxa, 2018)
We investigated phylogenetic relationships among populations of two species within the genus Leptophryne, L. cruentata and L. borbonica, using the mitochondrial 16S rRNA gene. As a result, we identified two distinct lineages within populations currently considered Leptophryne cruentata: 1) a lineage containing L. cruentata from the type locality, and 2) a lineage from Mt. Slamet and Mt. Ciremai. On the basis of genetic and morphological differences, we describe the Mt. Slamet and Mt. Ciremai populations as a new species, L. javanica sp. nov. The new species is distinguished from L. cruentata and L. borbonica by the following combination of morphological characters: the presence of distinct yellow mottling on the dorsum; relatively small body size (SVL male 22.2–24.0 mm, female 29.6 mm); relatively short hindlimbs (HLL 37.0–40.9 mm); relatively short fourth toe (4ToeL 4.3–6.0 mm); basal webbing on the hands, but well developed on toes; very protruding snout and an indistinct tympanum. In our preliminary phylogenetic analysis, we also detected four distinct lineages within Leptophryne borbonica: 1) a lineage containing true L. borbonica from west Java, 2) a lineage from Lampung (Sumatra I), 3) a lineage from northern Borneo, and 4) a lineage from Bengkulu (Sumatra II). Further studies are needed to determine taxonomic status of these lineages.